Molecular Genetic Analysis of Drought Stress Response Traits in Brachypodium spp. - Juan M. González; Jaime Redondo-Pedraza; Yolanda Loarce; Rifka Hammami; Eva Friero; Nicolás Jouve (Agronomy, 2020)
The root is the organ responsible for the uptake of water and therefore has a very important role in drought tolerance. The aims of the present work were to characterize nine traits of the root system architecture (RSA) and the shoot dry weight (W) of twelve genotypes of Brachypodium spp. under water stress and to establish the relationship between RSA phenotyping traits and SSRs. Two culture media, one standard (SM) and one (PEG) to induced water stress have been used. In SM medium, B. stacei had the highest values of W and all the RSA traits, except the mean diameter of the seminal roots, followed by B. hybridum and B. distachyon. In the PEG medium, root length increased in B. distachyon, decreased in B. hybridum and remained the same in B. stacei. A two-way hierarchical cluster analysis from 117 polymorphic SSRs and the traits of the RSA of the Brachypodium spp. genotypes, was performed. Brachypodium genotypes were separated into three groups corresponding to each species. In the second way of the hierarchical clustering association were observed between five RSA variables and SSR markers, which could be useful in the search for genes or QTLs related to RSA characters.